The subject in the existential phenomenology of Jean Paul Sartre - Álvarez González, Eduardo (Estudios de Filosofía, 2008)
The present article examines the concept of “subject” in Jean Paul Sastre`s thought. This examination, due to historical and conceptual reasons, is based directly and indirectly in both Heidegger and Husserl`s philosophies (and on other`s as well). Husserl`s Philosophy is the main foundation, which alternates with Sartre`s Philosophy, it is most important for the present text. So, the said analysis of the concept of “subject” and its implications and its phenomenological conceptualizations, is made undergoing the study of various forms of conscience: the conscience of the object, referred to something other than itself, and the conscience of oneself, which at the same time, is said in two different ways, that is: 1. as a reflexed, and not reflexive, conscience and 2. As reflexive conscience. Thanks to this said distinction and analysis of concepts such as I, conscience and subject, Sastre becomes a critic of Modern Philosophy of the Subject and, as a consequence of it, with sartrean thought one reaches the conviction that conscience is the only real, and not mere I. Therefore, the husserlian treatment of conscience – which Sastre will come to share -, understood as a constant intentional activity, will become, necessarily, in the priority of the subject since the sense of the phenomena originates, ultimately, in the subject.